The Analysis of Maternal Characteristics and Regulation of Antenatal Care on Pregnancy Risk Status Based on The Independent Family Health Evaluation (IFHE) - Diyan Indriyani; Esti Yunitasari; Ferry Efendi; Asmuji Asmuji; Sri Wahyuni Adriyani (Asia Pacific Journal of Health Management, 2023)
Background: High-risk pregnancy is a serious problem and needs to be detected early. Pregnant women with risk categories have a direct impact on the fetus. This study aimed to analyze maternal characteristics and the consistency of antenatal care visits in relation to the pregnancy risk status of pregnant women using the Independent Family Health Evaluation (IFHE)